2008
DOI: 10.1017/s1727719100002525
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of Elastic Waves by a Buried Tunnel Under Obliquely Incident Waves Using T Matrix

Abstract: This paper first studies the transition matrix formulation for the analysis of responses of an elastic halfspace with a buried tunnel subjected to obliquely incident waves. The basis functions are constructed using the moving P-, SV-, and SH-wave source potentials and to represent the scattered and refracted wave fields in series forms. The associated T-matrix expression of elastic inclusion is derived using Betti's third identity. Second, this study proposes a technique for calculating the integral representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In [17] an integral equation formulation was used to study the motion of the ground near a cavity and the stresses on the cavity wall and in [18] oblique incidence on a submerged, lined, cavity using a T-matrix formalism was considered. In neither case was any attempt made to study the far field.…”
Section: Introductionmentioning
confidence: 99%
“…In [17] an integral equation formulation was used to study the motion of the ground near a cavity and the stresses on the cavity wall and in [18] oblique incidence on a submerged, lined, cavity using a T-matrix formalism was considered. In neither case was any attempt made to study the far field.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the soil-structure interaction impacted the sound pressure field above the ground surface. Liao et al 6 analyzed the acoustic waves scattering by a buried tunnel applying the transition matrix (T-matrix) theory considering an oblique propagation of the incident wave to illustrate the scattered and refracted wave fields in series forms.…”
mentioning
confidence: 99%